Performance and prospects for Caribbean agriculture - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The Performance and Prospects for Caribbean Agriculture represents the Institute's first attempt at the collection and systematization of production and trade data, and institutional measures or agriculture at the regional level. The regional report covers the critical 1991-1995 period of adjustment for manu Caribbean countries. It is complemented by thirteen national reports, one per Caribbean country, which augment the information provided in the regional report. Information from counterpart institutions operating within the agricultural sector at the regional and hemispheric levels, was also used to augment the regional report in many respects.